Lymphocyte immunotherapy performed is pregnant gilts and sows did not affect preweaning mortality in the corresponding litters (1999)
ABSTRACT: This study was designed to test if lymphocyte immunotherapy (LI) of pregnant gilts and sows could improve preweaning mortality rates. In a commercial farm, Gilts (n = 61) first (n = 57) or second parity sows (n = 42) were selected and random assigned to treatment with saline (control group) or LI with lymphocytes obtained from multiparous sows, Boar, or growth-fattening pigs donors (alloimmunized groups). Treatments were performed at day 85 of pregnancy. Litter size and weight were evaluated by multifactor analysis of variance, whereas farrowing and preweaning mortality rates were analyzed by Mann-Whitney test. All traits evaluated at farrowing and at weaning did not significantly differ between groups (p > 0.05); when data from all immunized groups were altogether compared with control group (p > 0.5). Enteritis tended to be the most common cause of morbidity (p = 0.53). Mortality rate tended to increase in piglets from alloimmunized females (p = 0.12). The results suggest that LI of pregnant cross-bred gilts, first or second-parity sows did not affect preweaning mortality in piglets from subsequent lactation.